Enhancing the Concept of Numbers in Kindergarten with Graphic Media and Montessori Approachment - Rety, Dahniarti Cahyani; Masitoh, Siti; Arianto, Fajar (International Journal for Educational and Vocational Studies, 2020)
The background of this study by the achievement of cognitive development in this case the introduction of the concept of numbers has not been achieved. Problems that exist in group A Christian kindergarten LOGOS, when spelling out there are still children who haven't spelled out exactly, there are objects that are missed when spelling out and have not been able to show many objects in accordance with the symbol numbers, especially numbers 5, 6, 7, 8, 9, 10, this happens because there is no media in accordance with the theme of the lesson (land animals) and the method used is still in the form of assignments. The purpose of this study is to describe the increase in children's ability to recognize the concept of numbers through the use of graphic media and three-stage learning methods in the learning process. This study uses a class action research (CAR) method which is carried out in two cycles. Each cycle consists of four stages, namely the planning stage, the implementation phase, the observation and reflection stage. The subjects of the study were children of Group A Christian LOGOS Kindergarten consisting of 17 children. Data collection techniques in this study through observation and documentation. The results of the first cycle and second cycle of research showed an increase. The results showed that the use of graphic media and three-stage learning methods can improve the ability of children to recognize the concept of numbers, especially the numbers 5, 6, 7, 8, 9, 10 in group A children of Christian Kindergarten LOGOS.